Integrated Project in Separation Process Class as Innovative Tool to Improve Students’ Online Learning Experience (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2023)
Implementation of integrated project in chemical engineering courses has shown positive impact on students’ understanding, teamwork, critical thinking, and communication. In this case, an integrated project covering three different courses in chemical engineering, namely Reaction engineering, Process modelling and simulation, and Separation process was formulated on palm-oil based biodiesel production and introduced to students. The response from questionnaire was recorded and analyzed by using Excel software. More than 90% of students agree that the project helps them to understand the course and prepare for test or exam. While more than 70% of students want to see this type of project for other courses. Majority of students think that collaboration and teamwork help them to finish the project and doing integrated project saves their time to do assessment. Beside improving their soft skill like critical thinking, students can also sharpen their technical skills in solving the problems, especially on process flow drawing, operation of simulation tool, calculation technique, and search for suitable information and data. Through this integrated project, students could explore the connection among courses in Chemical Engineering program and implement the taught concepts in solving engineering problem, which can be challenging things to achieve during online learning.